High-content screening of active components of Traditional Chinese Medicine inhibiting TGF-β-induced cell EMT. Issue 8 (August 2022) - Xu, Mengzhen; Cui, Qinghua; Su, Wen; Zhang, Dan; Pan, Jiaxu; Liu, Xiangqi; Pang, Zheng; Zhu, Qingjun
Abstract: The epithelial mesenchymal transition (EMT) has roles in metastasis and invasion during fibrotic diseases and cancer progression. Some Traditional Chinese Medicines (TCMs) have shown inhibitory effects with respect to the EMT. The current study attempted to establish a multiparametric high-content method to screen for active monomeric compounds in TCM with the ability to target cellular EMT by assessing phenotypic changes. A total of 306 monomeric compounds from the MedChemExpress (MCE) compound library were screened by the high-content screening (HCS) system and 5 compounds with anti-EMT activity, including camptothecin (CPT), dimethyl curcumin (DMC), artesunate (ART), sinapine (SNP) and berberine (BER) were identified. To confirm anti-EMT activity, expression of EMT markers was assessed by qRT-PCR and Western blotting, and cell adhesion and migration measured by cell function assays. The results revealed that CPT, DMC, ART, SNP and BER inhibited transforming growth factor-β1 (TGF-β1)-induced expression of vimentin and α-SMA, upregulated expression of E-cadherin, increased cell adhesion and reduced cell migration. In summary, by quantifying the cell morphological changes during TGF-β1-induced EMT through multi-parametric analysis, TCM compounds with anti-EMT activity were successfully screened using the HCS system, a faster and more economical approach than conventional methods. Graphical abstract: Image 1 Abstract : High-content screening; Epithelial-mesenchymal transition; Traditional Chinese Medicine; TGF-β1.